Activity contexts and child-directed speech in socioeconomically diverse argentinian households - Rosemberg, Celia Renata (2023)
This study examines the quantity and quality of child-directed speech across household activities in a socioeconomically diverse sample of Argentinian Spanish-speaking children, an understudied population. Thirty children (mean: 14.3 months) and their families were audio-recorded for four hours. The middle two hours were transcribed and analysed using computerised language analysis (CLAN) to: (a) calculate lexical quantity (tokens) lexical diversity (VOCD) and syntactic complexity (MLU); (b) identify nouns and verbs. The procedures also involve the coding of regulative versus referential utterances and ongoing activities with defined spatial and temporal boundaries ?feeding, play, booksharing, grooming and household chores? as well as calculating the proportion of 21 types of concrete nouns and action verbs. Regression analysis showed effects of SES and type of activity on: (a) the quantity, lexical diversity and syntactic complexity of child-directed speech; (b) the proportion of referential and regulative utterances addressed to the child; (c) certain degree of semantic regularity in word-activity associations; and (d) an effect of SES on a variety of nouns and verbs (e.g. toys; utensils). These results highlight qualitative differences in input across daily activities and the contribution of SES to variance in lexical diversity and word semantics. Results provide evidence needed to inform public policies responsible for the promotion of early childhood language development and education.